Racial Differences in Bleeding Risks among Patients with Atrial Fibrillation: An Ecological Epidemiological Study Comparing Korea and UK Population - Kang, Dong-Seon; Yang, Pil-Sung; Kim, Daehoon; Jang, Eunsun; Yu, Hee Tae; Kim, Tae-Hoon; Sung, Jung Hoon; Pak, Hui-Nam; Lip, Gregory Y.H.; Joung, Boyoung (Thrombosis and Haemostasis, 2025)
Racial differences in the propensity to bleeding may be evident, with a higher risk of bleeding in Asian populations. This study aimed to assess racial differences in bleeding risk among patients with atrial fibrillation (AF) using an ecological epidemiological approach.We included patients with AF from the Korean National Health Insurance Service-Health Screening and UK Biobank who underwent health check-ups between 2006 and 2010. The analysis involved 1928 East Asians (62.1% male, median age 60.0 years) and 5917 White Europeans (71.4% male, median age 64.0 years) were analyzed. Primary outcome was composed of intracranial hemorrhage and bleeding from the gastrointestinal, respiratory, and genitourinary systems.During follow-up, the primary outcome occurred in 126 East Asians and 587 White Europeans. East Asians had a 42% lower 5-year incidence rate compared with White Europeans (weighted incidence rate 1.31 vs. 2.24 per 100 person-years; incidence rate ratio 0.58, 95% confidence interval: 0.41–0.83). Contrary to the primary outcome, the incidence of intracranial hemorrhage tended to be higher among East Asians (weighted incidence rate 0.34 vs. 0.14 per 100 person-years; incidence rate ratio 2.36, 95% confidence interval: 0.88–6.37). These results persisted even in patients naïve to antithrombotic drugs. East Asians who were already taking antithrombotic drugs at baseline showed no significant difference in the incidence of the primary outcome compared with White Europeans.This ecological study highlights racial differences in the incidence of bleeding influenced by anatomical site and antithrombotic drug use and underscores the necessity for race-based tailored approaches.
Keywords: racial difference; atrial fibrillation; intracranial hemorrhage; gastrointestinal bleeding